EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI RELASI DAN FUNGSI DITINJAU DARI KEMAMPUAN PENALARAN SISWA SMP NEGERI KELAS VIII DI KABUPATEN KARANGANYAR - Abdul Razak; Tri Atmojo Kusmayadi; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objective of this research was to investigate the effect of learning model toward learning outcomes in mathematics viewed from the reasoning ability. The learning models of this research were cooperative learning model of the GI with scientific, the cooperative learning model of the TPS with scientific, and the classical learning with scientific.This research used the quasi experimental research method with the factorial design of 3 x 3. Its population was all of the students in Grade VIII of State Junior Secondary Schools of Karanganyar. The samples of the research were taken by using the stratified cluster random sampling technique. The samples consisted of 280 students. The instruments used to gather the data were test of learning outcomes in mathematics and test of reasoning ability. The proposed hypotheses of the research were tested by using the two-way analysis of variance with unbalanced cells. The results of the research were as follows. 1) The students instructed with GI with scientific had a better learning outcomes in mathematics than those instructed TPS with scientific and those instructed the classical learning with scientific. Furthermore, the students instructed TPS with scientific had a better learning outcomes in mathematics than those instructed the classical learning model with scientific. 2) The learning outcomes in mathematics of the students with the high and moderate reasoning ability had a better than that of the students with the low reasoning ability. In addition, the students with the high reasoning ability had the same learning outcomes in mathematics as the students with the moderate reasoning ability. 3) On model of the GI with scientific, the students with the high and low reasoning ability had the same learning outcomes in mathematics as the students with the moderate reasoning ability. Moreover, the students with the high reasoning ability had a better learning outcomes in mathematics than those the students with the low reasoning ability. On model of the TPS with scientific and the classical learning with scientific results in the same learning outcomes in each of reasoning ability. 4) The students with the high reasoning ability, GI with scientific and the classical learning with scientific results in the same learning outcomes in mathematics as TPS with scientific. Furthermore, GI with scientific results in a better learning outcomes in mathematics than the classical learning with scientific. The students with the moderate and low reasoning ability had the same learning outcomes in each of learning model.Keywords: GI with scientific, TPS with scientific, learning outcomes, reasoning ability.